Employment Problems that Frequently Occur Between Workers and Work Worked with Incorrect Rewards or Payment - Cahyo Angger Marwadi; Arsyad Fakhri Zainuddin; Devani Yasmin Tarisya (Universitas Muhammadiyah Surakarta, 2022)
Discusses the problems faced by workers/laborers in Indonesia. To establish a harmonious relationship between workers and employers who provide employment opportunities for workers. Structurally, the workers are subordinated in determining everything. This position is used for the parties who hire to the detriment. This finally makes the workers want to uphold justice for them in the form of freedom in obtaining the rights they should be able to get. Good as treatment and wages for workers or workers. Even though there are not a few entrepreneurs who give good treatment to the workers, there are also many entrepreneurs who only care about the work of the workers by not paying attention to the interests of the workers, especially in Indonesia today. Therefore, if there is a problem between the entrepreneur and the worker/laborer, it should be resolved in a peaceful manner and also in a way that is in accordance with the legal rules for workers. Employers should also be able to listen more to the aspirations expressed by the workers in order to achieve mutual justice as well.